CORPORATE IDENTITY DESIGN IN THEORY AND PRACTICE - Losāne, Nataļja; Apele, Diāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of the article is to work out conception of the corporate identity design of Rezekne Academy of Technologies, having investigated the corporate identity design as the organization’s business card in the context of society. The article consists of an introduction, two parts and a conclusion. The introduction describes why the topic is actual, states the aim of the article and methods of investigation. The first part summarizes and analyzes the information about a corporate identity design. The second part describes the procedure of working out of the conception of the corporate identity design of RAT.The methods of research: theoretical – investigation and analysis of relevant literature, internet sources and regulatory documents. Empirical – methods of data collecting: group discussion; methods of data processing: comparative analysis, content analysis.